The Effect of Human Resource Development and Work Quality on Organizational Commitment with Work Strategy as an Intervening Variable in BPJS Ketenagakerjaan Jambi City Branch - Sari Puspita Dewi; Mesra B (International Journal of Management, Economic and Accounting, 2024)
This study aims to determine the Influence of Human Resource Development and Work Quality on Organizational Commitment with Work Strategy as an Intervening Variable in Bpjs Jambi City Branch, this study uses quantitative, primary data is also a source of data, the collection technique carried out is by distributing questionnaires to respondents, the population used is 60 employees, the sample used is all populations because it uses a saturated sample technique. The results of this study are as follows, Work quality has a positive and significant effect on Organizational Commitment with the original sample value of 0.070 and p values 0.362, Work Quality has a positive and significant effect on Work Strategy with the original sample of 0.462 and p values 0.000, Human Resource Development has a positive and significant effect on Organizational Commitment with the original sample of 0.371 and p values 0.014. Human resource development has a positive and significant effect on the Work Strategy with the original sample value of 0.440 and p values of 0.000. Work Strategy had a positive and significant effect on Organizational Commitment with an original sample value of 0.380 and p values of 0.012, Work Quality had a positive and significant effect on Organizational Commitment through Work Strategy with an original sample value of 0.175 and p values of 0.035. Human resource development has a positive and significant effect on Organizational Commitment through Work Strategy with an original sample value of 0.167 and p values of 0.029.